The Concept of Ulul Albab as Critical Thinking Behavior in the Perspective of the Qur'an - Huda, Mas Rukhin Lubabul (Al-Mudarris, 2025)
Islamic teachings in the Quran encourage every human being to think critically in their daily activities because humans are created by Allah as perfect beings. The purpose of this study is to explore the term Ulul Albab, examine the meaning of Ulul Albab, and explore the concept of Ulul Albab as critical thinking behavior from the perspective of the Quran. This research method uses a literature study method sourced from the Quran and its Tafsir as primary data, with books and scientific articles as secondary data. The results of this study are: (1) the phrase Ulul Albab appears 16 times in the Qur'an in 16 verses and 11 surahs, (2) the 16 verses containing the phrase Ulul Albab have different meanings, which can be broadly divided into two categories, namely the meaning of humans who have the intellect to remember and think, (3) Ulul Albab thinks critically in Q.S Ali Imran verse 190, where every human being must think critically about Allah's creation with their rational abilities, Q.S, Az-Zumar verse 18 thinks critically by scientifically examining arguments and accepting arguments as facts. This research contributes to the discussion of the concept of Ulul Albab with a focus on humans thinking critically about events created by Allah SWT. In addition, humans should avoid blind taqlid in seeking knowledge and should be able to think scientifically in their daily lives.